Association between grip strength and non-alcoholic fatty liver disease: A systematic review and meta-analysis - Han, Liu; Fu, Shifeng; Li, Jianglei; Liu, Deliang; Tan, Yuyong (Frontiers in Medicine, 2022)
Background The association between grip strength (GS) and non-alcoholic fatty liver disease (NAFLD) has been reported by recent epidemiological studies, however, the results of these studies are inconsistent. This meta-analysis was conducted to collect all available data and estimate the risk of NAFLD among people with low GS, as well as the risk of low GS among patients with NAFLD. Methods We systematically searched several literature databases including PubMed, Web of Science, Cochrane Library, and Embase from inception to March 2022. These observational studies reported the risk of NAFLD among people with low GS and/or the risk of low GS among patients with NAFLD. Qualitative and quantitative information was extracted, statistical heterogeneity was assessed using the I2 test, and potential for publication bias was assessed qualitatively by a visual estimate of a funnel plot and quantitatively by calculation of the Begg’s test and the Egger’s test. Results Of the citations, 10 eligible studies involving 76,676 participants met inclusion criteria. The meta-analysis of seven cross-section studies (69,757 participants) showed that people with low GS had increased risk of NAFLD than those with normal GS (summary OR = 3.32, 95% CI: 1.91–5.75). In addition, the meta-analysis of four studies (14,920 participants) reported that the risk of low GS patients with NAFLD was higher than those in normal people (summary OR = 3.31, 95% CI: 2.45–4.47). Conclusion In this meta-analysis, we demonstrated a strong relationship between low GS and NAFLD. We found an increased risk of NAFLD among people with low GS, and an increased risk of lower GS among NAFLD patients. Systematic review registration [www.crd.york.ac.uk/prospero], identifier [CRD42022334687].